Circular Integration of processes, industries, and economies. (June 2019) - Walmsley, Timothy Gordon; Ong, Benjamin H.Y.; Klemeš, Jiří Jaromír; Tan, Raymond R.; Varbanov, Petar Sabev
Abstract: Circular Economy has emerged as a popular research topic that is shaping public policy in Europe, China, America and elsewhere. It complements the conceptual basis of the Industrial Ecology framework, but places more emphasis on business models to create closed-loop material systems. However, the Circular Economy concept currently lacks robust engineering design methods, leading to many researchers question its effectiveness. In contrast, Process Integration is lesser known publicly, despite being widely applied in industry to achieve substantial reductions in industrial energy, water, and utility use. These three areas have developed in parallel with minimal cross-pollination, but are in fact potentially complementary. This contribution proposes the new unified concept of Circular Integration for greater transdisciplinary research cohesiveness in the sustainable development of processes, industries, and economies. Circular Integration combines elements from Process Integration, Industrial Ecology, and Circular Economy into a multi-dimensional, multi-scale approach to the minimisation of resource and energy consumption. Circular Integration thus provides an engineering toolbox for planning a Sustainable and Circular Economy. To demonstrate its potential, the paper presents a case study on sustainable biofuel production. The possible solution leverages existing industrial resources to potentially produce enough fuel to fulfil 37% of current demand for global air and marine transport. The Circular Integration framework can also be generalised to systems other than transport and energy, aiming to catalyse greater transdisciplinary research for the analysis, design, and implementation of sustainable and circular systems. Highlights: A new Circular Integration framework is developed to support a Circular Economy. The framework uses insights from Industrial Ecology and Process Integration. Its implementation creates new prospects for transdisciplinary research. Global air and marine transport is analysed to demonstrate the new framework.